Visão sistêmica da efetividade das normas de competência na busca de solução, pelo poder judiciário, para os conflitos ambientais - Rentroia, Cláudia Regina Lima (2012)
Since it became a reason of worldwide concern, environment has demanded from Brazilian public power a growing dedication towards the protection o f this diffuse right. The State powers find themselves involved with this munus, in order to fulfill their functions of organizing society and ensuring social peace. Many times, however, the latter can only be achieved by virtue of Judiciary action, since conflicts of interest are inherent to human relations. The object of this study was the exercise of jurisdictional function as a mean to reach effectiveness of competence regulation, in the search for solutions of environmental conflicts. Finally, some proposals are presented, aiming to contribute for the acquisition of a protective mentality. The purpose o f this is the fulfillment o f the constitutional command o f maintaining an ecologícally balanced environment for both present and future generations.